80.4k views
3 votes
How do I solve this equation?

\sqrt[3]{x - 5} = \sqrt[3]{4x + 1}

User Labeo
by
6.2k points

2 Answers

4 votes

Let's get rid of the cube roots. That will make the equations much easier to solve. To do this, we can cube both sides of the equation, as shown below:


(\sqrt[3]{x - 5})^3 = (\sqrt[3]{4x + 1})^3


x - 5 = 4x + 1


Now, we can easily solve the equation.


-5 = 3x + 1


-6 = 3x


\boxed{x = -2}


The equation has a solution of x = -2.

User Michael Hines
by
5.5k points
7 votes

Hey there!!

∛x - 5 = ∛ 4x + 1

Cube on both sides

x - 5 = 4x + 1

Add 5 on both sides

... x = 4x + 6

Subtract 4x on both sides

... -3x = 6

Divide by -3 on both sides

... x = 6 / -3

... x = -2

Hence, the final answer is -2.

Hope my answer helps!!

User Nazmus Saadat
by
6.2k points